Design of Microstrip Antenna Integrating 24 GHz and 77 GHz Compact High-Gain Arrays - Junli Zhu; Jingping Liu (Sensors)
The swift advancement of contemporary communication technology, along with the development of radar systems, has raised the requirements for antenna systems. In this work, an integrated array antenna operating in the 24 GHz and 77 GHz frequency bands is proposed. The microstrip antenna array element uses a width reduction approach to reduce its volume by 39.82%. By using corner series feeding, a 3 × 3 planar array is created. The arrays operating at 77 GHz and 24 GHz can produce gains of 14.19 dBi and 15.34 dBi, respectively, with sidelobe levels of less than −9.14 dB and −12.85 dB and cross-polarization levels of −29.26 dB and −40.52 dB. This design reduces the volume of the array, eliminates the need for a complex feeding network, minimizes feeding losses, and enhances the antenna’s gain, all while maintaining good sidelobe levels and cross-polarization performance. These improvements hold significant potential for broader application. Moreover, the simulation and measurement results are in close agreement.